We used to live here - Kliewer, Marcus (Emily Bestler Books, Atria, 2024)
A young, queer couple who flip houses, Charlie and Eve, while restoring an old house, answer the door to a man claiming to have lived there years before, which sets in motion a chain of uncanny and inexplicable events leading to Charlie's disappearance and Eve's descent into insanity.